Analysis of Oceanographic Physical Parameters at Sako Bungus Beach - Athiyyah Salwaa Andini; Nabila Afifah Azuga; Okta Rizal Karsih; Ronal Kurniawan; Fharisa Nabila Rizvi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2026)
This study was conducted at Sako Beach, Bungus Teluk Kabung District, Padang City, West Sumatra, to analyze the physical parameters of the water and examine changes in the shoreline occurring in the area. Data collection was conducted in November 2024 at five observation stations located using GPS. The measured parameters included water temperature, salinity, current velocity, and beach slope. The results showed that water temperatures ranged from 34 to 35°C, which is relatively high for tropical coastal waters. Salinity values ranged from 15 to 22 ppt, indicating brackish water characteristics and the influence of freshwater runoff from the land. Current velocity ranged from 0.1 to 0.25 m/s, falling into the category of weak to moderate currents, while the beach slope ranged from 0.744° to 2.919°, indicating a gently sloping beach. These physical conditions are interrelated and play a role in coastal dynamics, particularly in sediment distribution. Analysis of shoreline changes indicates that Sako Beach is undergoing accretion, or land gain, driven by sedimentation. The gentle slope influences this process, as does relatively low wave energy and the potential contribution of terrestrial runoff. The results of this study show that the dynamics of physical water parameters play a significant role in shaping changes in coastal morphology; therefore, periodic monitoring is necessary to support sustainable coastal zone management